Comedias y sainetes argentinos Antología 1 - Mazziotti, Nora (Colección Literaria LyC, 1996)
CONTIENE OBRAS DE: GRANADA, NICOLAS; PAYRO, ROBERTO J.; MERTENS, FEDERICO; BUTTARO, ENRIQUE; CAYOL, ROBERTO; BERRUTI, ALEJANDRO